Number 23 (February 1991) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1991)
(February 1991) - Life History of the Brighteye Darter Etheostoma lyceum (Pisces: Percidae), in Terrapin Creek, Kentucky. By D. Bell and T.J. Timmons, 6 pp. Species Dominance in the Fish Populations of the Pearl River at Two Study Areas in Mississippi and Louisiana: 1966-1988. By G.E. Gunning and R.D. Suttkus, 9 pp. Plus Minutes and Regional Reports.
Keywords: brighteye darter; etheostoma lyceum; pisces; percidae